2012
DOI: 10.1680/wama.2012.165.3.161
|View full text |Cite
|
Sign up to set email alerts
|

Stormwater treatment using permeable pavements

Abstract: Permeable pavements are generally used in water-sensitive urban design as a component of a treatment train and as a source control measure for reducing stormwater flows and pollutant loads. In Australia, permeable pavement systems are an emerging technology and consequently there are few installations more than 10 years old. The performance of permeable pavements in terms of treatment of urban stormwater runoff from a number of typical, but different urban catchments is discussed. Water quality monitoring was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
1
11

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 3 publications
0
26
1
11
Order By: Relevance
“…Legret and Colandini (1999) have specifically focussed on the behaviour of metals and by applying a mass balance scenario to a porous asphalt structure draining a street surface have determined that pollutant retention was mainly in the porous surface accounting for 89% of the incoming Pb but only 43%, 15% and 34% for Cu, Cd and Zn respectively. However, apart from Zn, these metal removal performances were considerably better than Beecham et al (2012) have reported for a car park draining through a permeable pavement structure (Cu, 3%; Ni, 18%; Pb, 9%; Zn, 38%). Collins et al (2008Collins et al ( , 2010 compared the hydrologic and nitrogen species removal of four types of permeable pavement (pervious concrete; interlocking pavers with small sized aggregate in the joints [12.9% and 8.5% open surface area]; concrete grid pavers filled with sand) with a standard asphalt surface in a 1 year old parking lot.…”
Section: Alternative Surface Structurescontrasting
confidence: 55%
See 2 more Smart Citations
“…Legret and Colandini (1999) have specifically focussed on the behaviour of metals and by applying a mass balance scenario to a porous asphalt structure draining a street surface have determined that pollutant retention was mainly in the porous surface accounting for 89% of the incoming Pb but only 43%, 15% and 34% for Cu, Cd and Zn respectively. However, apart from Zn, these metal removal performances were considerably better than Beecham et al (2012) have reported for a car park draining through a permeable pavement structure (Cu, 3%; Ni, 18%; Pb, 9%; Zn, 38%). Collins et al (2008Collins et al ( , 2010 compared the hydrologic and nitrogen species removal of four types of permeable pavement (pervious concrete; interlocking pavers with small sized aggregate in the joints [12.9% and 8.5% open surface area]; concrete grid pavers filled with sand) with a standard asphalt surface in a 1 year old parking lot.…”
Section: Alternative Surface Structurescontrasting
confidence: 55%
“…Boving et al (2008) highlighted that sand imported by cars to parking areas during winter conditions is a principal cause of clogging. The contamination of underlying soil and groundwater is a potential problem, particularly in car parks where high levels of soluble pollutants may occur (Beecham et al, 2012) and the installation of an impermeable membrane is recommended in such situations (Scholz and Grabowiecki, 2007). Concerns about the effectiveness of porous pavements in controlling stormwater runoff on clay soils was specifically tested by Dreelin et al (2006) who demonstrated a 93% runoff reduction for a plastic matrix filled with sand and planted with grass over a gravel base compared with a conventional asphalt surface.…”
Section: Alternative Surface Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the authors consider the laboratory-scale effectiveness of hydrous ferric oxide in the removal of heavy metals when subjected to intermittent loading. Results were positive and, similar to Beecham et al (2012) will be of interest and value to the practising water manager and academics alike.…”
mentioning
confidence: 56%
“…In the first of the two papers, Beecham et al (2012) present valuable data on the extent to which pollutant removal occurs in a permeable pavement system compared to a conventional pavement when treating rainfall runoff of varying quality. Although permeable pavement technology has been with us for 20 years, the uptake has been limited and sporadic.…”
mentioning
confidence: 99%